Styrene-acrylonitrile-maleic anhydride copolymer sizing agent as well as preparation method and application thereof
By mixing styrene-acrylonitrile-maleic anhydride copolymer with aqueous emulsifier and epoxy resin to prepare a sizing agent, the problem of insufficient processing performance of carbon fiber is solved, the heat resistance and mechanical properties of composite materials are improved, and carbon fiber is realized Good bonding to the resin matrix.
Patent Information
- Application Number
- CN202310814305.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-07
AI Technical Summary
In the prior art, when preparing high-temperature resistant composite materials, the processing performance of carbon fibers is insufficient, which affects the mechanical properties and bonding strength of the material.
The slurry agent is prepared by mixing styrene-acrylonitrile-maleic anhydride copolymer with aqueous emulsifier and epoxy resin, and plasticizer and surfactant are added to improve the hydrophilicity and high temperature resistance of the copolymer through polymerization and hydrolysis treatment. performance, forming a sizing agent with good affinity.
It significantly improves the processing performance of carbon fiber, improves the heat resistance and mechanical properties of composite materials, enhances the bonding strength between carbon fiber and resin matrix, and has a simple process and high repeatability. It is suitable for different types of resin matrix.
Smart Images

Figure CN119265937A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of fiber manufacturing, in particular to a styrene-acrylonitrile-maleic anhydride copolymer sizing agent and a preparation method and application thereof. Background Art
[0002] Carbon fiber and graphite fiber are widely used in aerospace, national defense and military fields. The carbon content of carbon fiber is more than 90%, and the carbon content of graphite fiber is more than 99%. Both fibers have a layered hexagonal lattice graphite structure inside, which can withstand high temperatures above 2000°C, and have good properties such as low density, high modulus, and high tensile strength. Therefore, they can be used as reinforcements and composite materials made of resins, ceramics, metals or rubber as matrices. Styrene-acrylonitrile-maleic anhydride copolymer (SAM) is a thermoplastic resin copolymerized by three monomers: styrene, maleic anhydride and acrylonitrile. SAM has the characteristics of good heat resistance, high compatibility, and high light transmittance. It can be used in the preparation of medical equipment, heat-resistant materials, electrical accessories and other fields. SAM can be combined with carbon fiber and graphite fiber to prepare composite materials. Carbon fiber and graphite fiber can improve the mechanical properties of composite materials, so they are used in the field of high-temperature resistant composite materials. Polymers containing maleic anhydride can be hydrolyzed to make the polymer have carboxyl groups, and salt treatment can make the polymer have good hydrophilicity, so it can be used in the field of hydrophilic materials.
[0003] Patent CN109021156A discloses a low-yellowness styrene-acrylonitrile-maleic anhydride copolymer and a preparation method thereof. In the patent, styrene, maleic acid, acrylonitrile and a fourth monomer are copolymerized, and a bulk polymerization method is adopted to solve the problems of excessive yellowing of the SAM resin and affecting the appearance of the product. By adding an oil-soluble initiator, the polymerization reaction can be carried out at a lower temperature, thereby reducing the molecular weight of the polymer. Summary of the invention
[0004] The invention prepares a styrene-acrylonitrile-maleic anhydride copolymer sizing agent by mixing a styrene-acrylonitrile-maleic anhydride copolymer, an aqueous emulsifier and an epoxy resin. The polymerization ratio of the SAM resin in the sizing agent is adjustable, the sizing agent has good affinity with the styrene-acrylonitrile-maleic anhydride copolymer and the epoxy resin, and has good high temperature resistance, and has good application prospects in the field of preparing composite materials.
[0005] One of the purposes of the present invention is to provide a styrene-acrylonitrile-maleic anhydride copolymer sizing agent, comprising styrene-acrylonitrile-maleic anhydride copolymer, an aqueous emulsifier, an epoxy resin, an auxiliary agent and water. The auxiliary agent comprises a plasticizer and a surfactant.
[0006] The styrene-acrylonitrile-maleic anhydride copolymer preferably has a structure shown in formula (I):
[0007]
[0008] wherein the degree of polymerization m is 1 to 50; n is 1 to 50; o is 1 to 50;
[0009] R 1 for
[0010] R 2 for
[0011] R 3 for
[0012] R 4 , R 5 , R 6 Each is independently -H, -CH 3 , -F, -Cl, -Br or
[0013] R 7 H, Na, K, NH 4 or NH(CH 3 ) 3 ;
[0014] R 8 -H, -CH 3 or -Cl.
[0015] Preferably, in the technical solution, R in the formula (I) 1 , R 2 , R 3 Can be in any order, such as R 1 -R 2 -R 3 , R 1 -R 3 -R 2 wait.
[0016] The epoxy resin is preferably at least one of bisphenol A epoxy resin, bisphenol F epoxy resin and bisphenol S epoxy resin.
[0017] The plasticizer is preferably at least one of dioctyl adipate, dioctyl phthalate, diisononyl phthalate and dioctyl sebacate.
[0018] The surfactant is preferably at least one of oleic acid, potassium oleate and sodium oleate.
[0019] The mass ratio of styrene-acrylonitrile-maleic anhydride copolymer to the aqueous emulsifier is (1-10):1, preferably (3-6):1, for example, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc.
[0020] The mass ratio of the epoxy resin to the aqueous emulsifier is (0.2-2):1, preferably (0.5-1):1, for example, 0.2:1, 0.5:1, 1:1, 2:1, etc.
[0021] The mass ratio of the plasticizer to the aqueous emulsifier is (0.005-0.05):1, preferably (0.02-0.03):1, for example, it can be 0.005, 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, etc.
[0022] The mass ratio of the surfactant to the aqueous emulsifier is (0.01-0.1):1, preferably (0.04-0.06):1, for example, 0.01:1, 0.02:1, 0.04:1, 0.05:1, 0.06:1, 0.08:1, 0.1:1, etc.
[0023] The solid content of the sizing agent is 10-50wt%, for example, 10wt%, 20wt%, 30wt%, 40wt%, 50wt% and the like.
[0024] The styrene-acrylonitrile-maleic anhydride copolymer is obtained by polymerizing styrene monomers, acrylonitrile and maleic anhydride monomers and then hydrolyzing them.
[0025] The aqueous emulsifier is prepared from components including bisphenol A epoxy resin and polyethylene glycol.
[0026] The invention provides a styrene-acrylonitrile-maleic anhydride copolymer (SAM) sizing agent, which has good affinity with epoxy resin and can effectively improve the processing performance of carbon fiber. The invention can be applied to different types of resin matrices by changing the structure of the resin in the main agent of the sizing agent and the proportion of the components.
[0027] The second object of the present invention is to provide a method for preparing the styrene-acrylonitrile-maleic anhydride copolymer sizing agent, comprising the following steps:
[0028] The aqueous emulsifier, styrene-acrylonitrile-maleic anhydride copolymer, epoxy resin and solvent are mixed, auxiliary agent and water are added, the solvent is removed, and emulsification is performed.
[0029] The mass ratio of the solvent to the aqueous emulsifier is (2-20):1, preferably (5-10):1, for example, 2:1, 5:1, 10:1, 15:1, 20:1, etc.
[0030] Preferably, the aqueous emulsifier, styrene-acrylonitrile-maleic anhydride copolymer, epoxy resin and solvent are mixed and stirred for 0.2 to 1 hour.
[0031] Preferably, the emulsification is carried out at 3000-11000 rpm for 0.2-2 hours.
[0032] The solvent may be acetone or the like, and the solvent may be removed by methods such as reduced pressure distillation.
[0033] The styrene-acrylonitrile-maleic anhydride copolymer is obtained by polymerizing styrene monomers, acrylonitrile and maleic anhydride monomers and then hydrolyzing them.
[0034] According to a preferred embodiment of the present invention, the styrene-acrylonitrile-maleic anhydride copolymer can be prepared by the following steps: mixing a styrene monomer, a maleic anhydride monomer, acrylonitrile, an initiator and a solvent 1, performing a polymerization reaction, removing the solvent 1 after the reaction, adding water and a neutralizing agent for a hydrolysis reaction, and finally removing the water.
[0035] Preferably, the styrene monomer is at least one of styrene, 4-methylstyrene, 4-fluorostyrene, 3-fluorostyrene, 4-bromostyrene, 2-chlorostyrene and 4-tert-butylstyrene.
[0036] Preferably, the maleic anhydride monomer is at least one of maleic anhydride, 2,3-dimethylmaleic anhydride, methylmaleic anhydride and 2,3-dichloromaleic anhydride.
[0037] Preferably, the neutralizing agent is at least one of sodium hydroxide, potassium hydroxide, ammonia water and triethylamine.
[0038] The initiator may be a common initiator in the art, such as azobisisobutyronitrile, etc. There is no particular limitation on the amount of the initiator, which is a conventional amount in the art.
[0039] The solvent 1 can be selected from common solvents in the art, such as dimethyl sulfoxide, etc. There is no particular limitation on the amount of the solvent used, which is a conventional amount in the art.
[0040] In the above steps of preparing the styrene-acrylonitrile-maleic anhydride copolymer,
[0041] The polymerization reaction temperature is 60 to 90° C., and the polymerization reaction time is 2 to 8 hours;
[0042] The mass ratio of maleic anhydride monomer to styrene monomer is (0.05-1):1, preferably (0.1-0.5):1, for example, 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, etc.;
[0043] The mass ratio of acrylonitrile to styrene monomer is (0.1-2):1, preferably (0.2-1):1, for example, 0.1:1, 0.2:1, 0.4:1, 0.6:1, 0.8:1, 1:1, 1.2:1, 1.4:1, 1.6:1, 1.8:1, 2:1, etc.;
[0044] The temperature of the hydrolysis reaction is 20 to 40° C., and the time of the hydrolysis reaction is 1 to 3 hours;
[0045] The mass ratio of water to styrene monomer is (0.5-5):1, preferably (1-3):1, for example, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, etc.;
[0046] The mass ratio of the neutralizer to the styrene monomer is (0.05-5):1, preferably (0.1-1):1, for example, 0.05:1, 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, etc.
[0047] The aqueous emulsifier is prepared from components including bisphenol A epoxy resin and polyethylene glycol.
[0048] According to a preferred embodiment of the present invention, the aqueous emulsifier is prepared by the following steps: polyethylene glycol, bisphenol A epoxy resin and potassium persulfate are mixed at 100 to 150° C. and reacted for 1 to 10 hours.
[0049] Preferably, the polyethylene glycol is at least one of polyethylene glycol-200, polyethylene glycol-400, polyethylene glycol-600, polyethylene glycol-800, polyethylene glycol-1000, polyethylene glycol-1500, polyethylene glycol-2000, and polyethylene glycol-4000.
[0050] Preferably, the bisphenol A epoxy resin is at least one of E-44, E-51, and E-55.
[0051] In the above steps of preparing the aqueous emulsifier,
[0052] The mass ratio of polyethylene glycol to bisphenol A epoxy resin is (0.5-5):1, for example, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, etc.;
[0053] The mass ratio of potassium persulfate to bisphenol A epoxy resin is (0.005-0.05):1, for example, 0.005:1, 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, etc.;
[0054] After the reaction is completed, acetone can be used to remove potassium persulfate, and the acetone can be removed by distillation under reduced pressure.
[0055] The third object of the present invention is to provide the use of the styrene-acrylonitrile-maleic anhydride copolymer sizing agent or the sizing agent obtained by the preparation method in fiber composite materials.
[0056] The prepared SAM sizing agent is diluted to 1-5%, used for sizing carbon fiber or graphite fiber, dried at 110-160° C., and collected into fibers.
[0057] The sizing agent of the present invention has moderate sizing amount (0.6-1.5%), low saturated water absorption (<0.1%), appropriate interlaminar shear strength (70-110MPa), moderate particle size (200-500nm) and good stability (>6 months).
[0058] The styrene-acrylonitrile-maleic anhydride copolymer sizing agent of the present invention has good affinity with styrene-acrylonitrile-maleic anhydride copolymer, has good compatibility with high temperature resistant resin matrices such as thermosetting and thermoplastic, and can simultaneously play the role of improving the heat resistance of carbon fiber composite materials, improving the mechanical properties of carbon fiber, and strengthening the bonding strength of carbon fiber and resin matrix. The sizing agent can give carbon fiber good sizing performance, sufficient clustering and low sizing adhesion. The present invention is simple in process, high in repeatability, and can meet the market demand for SAM sizing agents.
[0059] The present invention is characterized by:
[0060] (1) The styrene-acrylonitrile-maleic anhydride in the main agent introduces carboxyl groups into the main chain of the copolymer, and sodium hydroxide is used to hydrolyze some of the carboxyl groups into salts, thereby improving the hydrophilicity of the SAM copolymer. The introduction of carboxyl groups can also make the SAM copolymer have good affinity with the fiber surface and resin, thereby preparing high-performance composite materials.
[0061] (2) Styrene-acrylonitrile-maleic anhydride copolymers have good high-temperature performance and can form a high-temperature resistant resin layer on the fiber surface, so that the prepared fiber composite material has good high-temperature resistance.
[0062] (3) The various components of the sizing agent can be adjusted according to the use of the sizing agent. The molecular weight of polyethylene glycol, the types and amounts of surfactants and plasticizers can be adjusted according to the use conditions. The particle size of the sizing agent emulsion can be adjusted according to the use environment, thereby improving the sizing performance of the sizing agent. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 This is the particle size distribution of the sizing agent in Example 1. DETAILED DESCRIPTION
[0064] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0065] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0066] According to a preferred embodiment of the present invention, the preparation method of the styrene-acrylonitrile-maleic anhydride copolymer sizing agent can be:
[0067] Step a) at room temperature and nitrogen atmosphere, based on the amount of added styrene monomers, the mass ratio of maleic anhydride monomer to styrene monomer is 0.05:1-1:1, the mass ratio of acrylonitrile to styrene monomer is 0.1:1-2:1, the mass ratio of azobisisobutyronitrile to styrene monomer is 0.01:1-0.1:1, and the mass ratio of dimethyl sulfoxide to styrene monomer is 1:1-10:1. Styrene monomers, maleic anhydride monomers, acrylonitrile, azobisisobutyronitrile and dimethyl sulfoxide are added to a reactor, react at 60-90° C. for 2-8 hours, and then remove dimethyl sulfoxide by reduced pressure distillation. Water and a neutralizer are added to a reactor at a mass ratio of water to styrene monomer of 0.5:1-5:1 and a mass ratio of a neutralizer to styrene monomer of 0.05:1-5:1, and react at room temperature for 1-3 hours, and then remove water by reduced pressure distillation to obtain a SAM resin.
[0068] Step b) at 100-150° C., based on the amount of bisphenol A epoxy resin added, the mass ratio of polyethylene glycol to bisphenol A epoxy resin is 0.5:1-5:1, and the mass ratio of potassium persulfate to bisphenol A epoxy resin is 0.005:1-0.05:1, bisphenol A epoxy resin, polyethylene glycol and potassium persulfate are added into a reactor, react for 1-10 hours, cool to room temperature, add acetone into the reactor at a mass ratio of acetone to styrene of 0.5:1-5:1, filter, and remove acetone in the filtrate by reduced pressure distillation to obtain an aqueous emulsifier.
[0069] Step c) at room temperature, based on the amount of the added aqueous emulsifier, the mass ratio of SAM resin to aqueous emulsifier is 1:1-10:1, the mass ratio of epoxy resin to aqueous emulsifier is 0.2:1-2:1, and the mass ratio of acetone to aqueous emulsifier is 2:1-20:1, and the aqueous emulsifier, the aqueous emulsifier, the SAM resin, the epoxy resin and the acetone are added to the reactor, and stirred for 0.2-1 hour, based on the amount of the added aqueous emulsifier, the mass ratio of plasticizer to aqueous polyurethane is 0.005:1-0.05:1, and the mass ratio of surfactant to aqueous polyurethane is 0.01:1-0.1:1, the plasticizer and the surfactant are added to the reactor, water is added to dilute the mixed system to a solid content of 10%-50%, acetone is removed by reduced pressure distillation, and emulsification is carried out at 3000-11000rpm for 0.2-2 hours to obtain a SAM sizing agent.
[0070] The styrene monomer described in step a) of the preparation method of the sizing agent is one of styrene, 4-methylstyrene, 4-fluorostyrene, 3-fluorostyrene, 4-bromostyrene, 2-chlorostyrene, and 4-tert-butylstyrene, the maleic anhydride monomer is one of maleic anhydride, 2,3-dimethylmaleic anhydride, methylmaleic anhydride, and 2,3-dichloromaleic anhydride, and the neutralizer is one of sodium hydroxide, potassium hydroxide, ammonia water, and triethylamine. The polyethylene glycol described in step b) is one of polyethylene glycol-200, polyethylene glycol-400, polyethylene glycol-600, polyethylene glycol-800, polyethylene glycol-1000, polyethylene glycol-1500, polyethylene glycol-2000, and polyethylene glycol-4000, and the bisphenol A epoxy resin is at least one of E-44, E-51, and E-55. The epoxy resin described in step c) is one of bisphenol A epoxy resin, bisphenol F epoxy resin, and bisphenol S epoxy resin, the surfactant is one of oleic acid, potassium oleate, and sodium oleate, and the plasticizer is one of dioctyl adipate, dioctyl phthalate, diisononyl phthalate, and dioctyl sebacate.
[0071] Test method:
[0072] The sizing amount and saturated water absorption of the sizing carbon fiber were tested, and the interlaminar shear strength (ILSS) test was carried out according to JC / T773-2010. The resin used in the ILSS test was epoxy resin.
[0073] The particle size was measured using a Malvern Mastersizer 3000.
[0074] Embodiment 1:
[0075] At room temperature and nitrogen atmosphere, 8.33 g of styrene, 1.96 g of maleic anhydride, 5.31 g of acrylonitrile, 0.16 g of azobisisobutyronitrile and 31.2 g of dimethyl sulfoxide were added to a reactor. After reacting at 65° C. for 3 hours, dimethyl sulfoxide was removed by vacuum distillation. 20 g of water and 4.05 g of triethylamine were added, and the mixture was stirred at room temperature for 2 hours. Water was removed by vacuum distillation to obtain 19.6 g of SAM resin.
[0076] At 120°C, 6.8 g of bisphenol A epoxy resin, 20 g of polyethylene glycol (PEG-2000) and 0.12 g of potassium persulfate were added to a reactor and stirred for 8 hours. The mixture was cooled to room temperature, 10 g of acetone was added, filtered, and acetone in the filtrate was removed by vacuum distillation to obtain 26.8 g of an aqueous emulsifier.
[0077] At room temperature, 19.6 g of SAM resin, 4.46 g of aqueous emulsifier and 2.55 g of bisphenol A epoxy resin were added to a reactor, and 30 g of acetone was added, stirred for 0.5 hour, and then 0.1 g of dioctyl adipate and 0.2 g of sodium oleate were added, and water was added to dilute the mixed system to a solid content of 20%, and acetone was removed by vacuum distillation. The mixture was emulsified at 10000 rpm for 1 hour to obtain 134.8 g of SAM sizing agent.
[0078] The prepared SAM sizing agent in this embodiment is diluted to 2%, used for sizing carbon fiber on a carbon fiber production line, dried at 120° C., and collected. The sizing adhesion of the sizing carbon fiber is 1.2%, the saturated water absorption is 0.08%, and the ILSS is 81 MPa.
[0079] Embodiment 2:
[0080] At room temperature and nitrogen atmosphere, 7.29 g of styrene, 2.94 g of maleic anhydride, 5.31 g of acrylonitrile, 0.16 g of azobisisobutyronitrile and 31.08 g of dimethyl sulfoxide were added into a reactor. After reacting at 65°C for 3 hours, dimethyl sulfoxide was removed by vacuum distillation. 20 g of water and 6.07 g of triethylamine were added, stirred at room temperature for 2 hours, and water was removed by vacuum distillation to obtain 21.6 g of SAM resin.
[0081] At 120°C, 6.8 g of bisphenol A epoxy resin, 20 g of polyethylene glycol (PEG-2000) and 0.12 g of potassium persulfate were added to a reactor and stirred for 8 hours. The mixture was cooled to room temperature, 10 g of acetone was added, filtered, and acetone in the filtrate was removed by vacuum distillation to obtain 26.8 g of an aqueous emulsifier.
[0082] At room temperature, 21.6 g of SAM resin, 4.46 g of aqueous emulsifier and 2.55 g of bisphenol A epoxy resin were added to a reactor, and 30 g of acetone was added, stirred for 0.5 hour, and then 0.1 g of dioctyl adipate and 0.2 g of sodium oleate were added, and water was added to dilute the mixed system to a solid content of 20%, and acetone was removed by vacuum distillation. The mixture was emulsified at 10000 rpm for 1 hour to obtain 144.6 g of SAM sizing agent.
[0083] The SAM sizing agent prepared in this embodiment is diluted to 2%, used for sizing carbon fiber on a carbon fiber production line, dried at 120° C., and collected. The sizing adhesion of the sizing carbon fiber is 1.1%, the saturated water absorption is 0.07%, and the ILSS is 80 MPa.
[0084] Embodiment 3:
[0085] At room temperature and nitrogen atmosphere, 10.42 g of styrene, 1.96 g of maleic anhydride, 4.24 g of acrylonitrile, 0.16 g of azobisisobutyronitrile and 31.2 g of dimethyl sulfoxide were added to a reactor. After reacting at 65° C. for 3 hours, dimethyl sulfoxide was removed by vacuum distillation. 20 g of water and 4.05 g of triethylamine were added, and the mixture was stirred at room temperature for 2 hours. Water was removed by vacuum distillation to obtain 20.6 g of SAM resin.
[0086] At 120°C, 6.8 g of bisphenol A epoxy resin, 20 g of polyethylene glycol (PEG-2000) and 0.12 g of potassium persulfate were added to a reactor and stirred for 8 hours. The mixture was cooled to room temperature, 10 g of acetone was added, filtered, and acetone in the filtrate was removed by vacuum distillation to obtain 26.8 g of an aqueous emulsifier.
[0087] At room temperature, 20.6 g of SAM resin, 4.46 g of aqueous emulsifier and 2.55 g of bisphenol A epoxy resin were added to a reactor, and 30 g of acetone was added, stirred for 0.5 hour, and then 0.1 g of dioctyl adipate and 0.2 g of sodium oleate were added, and water was added to dilute the mixed system to a solid content of 20%, and acetone was removed by vacuum distillation. The mixture was emulsified at 10000 rpm for 1 hour to obtain 139.9 g of SAM sizing agent.
[0088] The prepared SAM sizing agent in this embodiment is diluted to 2%, used for sizing carbon fiber on a carbon fiber production line, dried at 120° C., and collected. The sizing carbon fiber has a sizing adhesion of 1.0%, a saturated water absorption of 0.11%, and an ILSS of 78 MPa.
[0089] Embodiment 4:
[0090] At room temperature and in a nitrogen atmosphere, 9.55 g of 4-methylstyrene, 1.96 g of maleic anhydride, 5.31 g of acrylonitrile, 0.16 g of azobisisobutyronitrile and 31.2 g of dimethyl sulfoxide were added to a reactor. After reacting at 65° C. for 3 hours, dimethyl sulfoxide was removed by distillation under reduced pressure. 20 g of water and 1.6 g of sodium hydroxide were added, and the mixture was stirred at room temperature for 2 hours. Water was removed by distillation under reduced pressure to obtain 18.32 g of SAM resin.
[0091] At 120°C, 6.8 g of bisphenol A epoxy resin, 20 g of polyethylene glycol (PEG-2000) and 0.12 g of potassium persulfate were added to a reactor and stirred for 8 hours. The mixture was cooled to room temperature, 10 g of acetone was added, filtered, and acetone in the filtrate was removed by vacuum distillation to obtain 26.8 g of an aqueous emulsifier.
[0092] At room temperature, 18.32 g of SAM resin, 4.46 g of aqueous emulsifier and 2.55 g of bisphenol A epoxy resin were added to a reactor, and 30 g of acetone was added, stirred for 0.5 hour, and then 0.1 g of dioctyl adipate and 0.2 g of sodium oleate were added. Water was added to dilute the mixture to a solid content of 20%, acetone was removed by reduced pressure distillation, and emulsification was carried out at 10000 rpm for 1 hour to obtain 128.15 g of SAM sizing agent.
[0093] The prepared SAM sizing agent in this embodiment is diluted to 2%, used for sizing carbon fiber on a carbon fiber production line, dried at 120° C., and collected. The sizing adhesion of the sizing carbon fiber is 1.2%, the saturated water absorption is 0.09%, and the ILSS is 83 MPa.
[0094] Embodiment 5:
[0095] At room temperature and nitrogen atmosphere, 8.33 g of styrene, 1.96 g of maleic anhydride, 5.31 g of acrylonitrile, 0.16 g of azobisisobutyronitrile and 31.2 g of dimethyl sulfoxide were added to a reactor. After reacting at 65° C. for 3 hours, dimethyl sulfoxide was removed by vacuum distillation. 20 g of water and 4.05 g of triethylamine were added, and the mixture was stirred at room temperature for 2 hours. Water was removed by vacuum distillation to obtain 19.6 g of SAM resin.
[0096] At 120°C, 6.8 g of bisphenol A epoxy resin, 15 g of polyethylene glycol (PEG-1500) and 0.12 g of potassium persulfate were added to a reactor and stirred for 8 hours. The mixture was cooled to room temperature, 10 g of acetone was added, the mixture was filtered, and the acetone in the filtrate was removed by vacuum distillation to obtain 21.8 g of an aqueous emulsifier.
[0097] At room temperature, 19.6 g of SAM resin, 3.63 g of aqueous emulsifier and 2.55 g of bisphenol A epoxy resin were added to a reactor, and 30 g of acetone was added, stirred for 0.5 hour, and then 0.1 g of dioctyl adipate and 0.2 g of sodium oleate were added, and water was added to dilute the mixed system to a solid content of 20%, and acetone was removed by vacuum distillation. The mixture was emulsified at 10000 rpm for 1 hour to obtain 130.65 g of SAM sizing agent.
[0098] The prepared SAM sizing agent in this embodiment is diluted to 2%, used for sizing carbon fiber on a carbon fiber production line, dried at 120° C., and collected. The sizing adhesion of the sizing carbon fiber is 1.3%, the saturated water absorption is 0.07%, and the ILSS is 85 MPa.
[0099] Comparative Example 1:
[0100] At room temperature and nitrogen atmosphere, 8.33 g of styrene, 1.96 g of maleic anhydride, 5.31 g of acrylonitrile, 0.16 g of azobisisobutyronitrile and 31.2 g of dimethyl sulfoxide were added to a reactor. After reacting at 65° C. for 3 hours, dimethyl sulfoxide was removed by vacuum distillation. 20 g of water and 4.05 g of triethylamine were added, and the mixture was stirred at room temperature for 2 hours. Water was removed by vacuum distillation to obtain 19.6 g of SAM resin.
[0101] At room temperature, 19.6 g of SAM resin, 3.33 g of polyethylene glycol (PEG-2000) and 2.55 g of bisphenol A epoxy resin were added to a reactor, and 30 g of acetone was added, stirred for 0.5 hour, and then 0.1 g of dioctyl adipate and 0.2 g of sodium oleate were added. Water was added to dilute the mixture to a solid content of 20%, and acetone was removed by vacuum distillation. The mixture was emulsified at 10,000 rpm for 1 hour to obtain 129.15 g of SAM sizing agent.
[0102] The prepared SAM sizing agent in this embodiment is diluted to 2%, used for sizing carbon fiber on a carbon fiber production line, dried at 120° C., and collected. The sizing adhesion of the sizing carbon fiber is 1.2%, the saturated water absorption is 0.22%, and the ILSS is 31 MPa.
Claims
1. A styrene-acrylonitrile-maleic anhydride copolymer sizing agent, comprising styrene-acrylonitrile-maleic anhydride copolymer, an aqueous emulsifier, an epoxy resin, an auxiliary agent and water, wherein the auxiliary agent comprises a plasticizer and a surfactant.
2. The sizing agent according to claim 1, characterized in that: The styrene-acrylonitrile-maleic anhydride copolymer has a structure shown in formula (I): Wherein m is 1 to 50; n is 1 to 50; o is 1 to 50; R1 is R2 is R3 is R4, R5, R6 are each independently -H, -CH3, -F, -Cl, -Br or R7 is H, Na, K, NH4 or NH(CH3)3; R8 is -H, -CH3 or -Cl.
3. The sizing agent according to claim 1, characterized in that: The epoxy resin is at least one of bisphenol A epoxy resin, bisphenol F epoxy resin and bisphenol S epoxy resin; and / or The plasticizer is at least one of dioctyl adipate, dioctyl phthalate, diisononyl phthalate and dioctyl sebacate; and / or The surfactant is at least one of oleic acid, potassium oleate and sodium oleate.
4. The sizing agent according to claim 1, characterized in that: The mass ratio of styrene-acrylonitrile-maleic anhydride copolymer to the aqueous emulsifier is (1-10):1, preferably (3-6):1; The mass ratio of epoxy resin to aqueous emulsifier is (0.2-2):1, preferably (0.5-1):1; The mass ratio of the plasticizer to the aqueous emulsifier is (0.005-0.05):1, preferably (0.02-0.03):1; The mass ratio of the surfactant to the aqueous emulsifier is (0.01-0.1):1, preferably (0.04-0.06):1; The solid content of the sizing agent is 10-50wt%.
5. A method for preparing the styrene-acrylonitrile-maleic anhydride copolymer sizing agent according to any one of claims 1 to 4, comprising the following steps: The aqueous emulsifier, styrene-acrylonitrile-maleic anhydride copolymer, epoxy resin and solvent are mixed, auxiliary agent and water are added, the solvent is removed, and emulsification is performed.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the solvent to the aqueous emulsifier is (2-20):1, preferably (5-10):1; and / or, Emulsify at 3000-11000 rpm for 0.2-2 hours.
7. The preparation method according to claim 5, characterized in that: The styrene-acrylonitrile-maleic anhydride copolymer is obtained by polymerizing styrene monomers, acrylonitrile and maleic anhydride monomers and then hydrolyzing them; and / or, The aqueous emulsifier is prepared from components including bisphenol A epoxy resin and polyethylene glycol.
8. The preparation method according to claim 7, characterized in that: The styrene-acrylonitrile-maleic anhydride copolymer is prepared by the following steps: mixing a styrene monomer, a maleic anhydride monomer, acrylonitrile, an initiator and a solvent 1 to carry out a polymerization reaction, removing the solvent 1 after the reaction is completed, and adding water and a neutralizing agent to carry out a hydrolysis reaction; Preferably, the styrene monomer is at least one of styrene, 4-methylstyrene, 4-fluorostyrene, 3-fluorostyrene, 4-bromostyrene, 2-chlorostyrene and 4-tert-butylstyrene; the maleic anhydride monomer is at least one of maleic anhydride, 2,3-dimethylmaleic anhydride, methylmaleic anhydride and 2,3-dichloromaleic anhydride; the neutralizing agent is at least one of sodium hydroxide, potassium hydroxide, ammonia water and triethylamine; and / or, Preferably, the polymerization reaction temperature is 60 to 90° C., and the polymerization reaction time is 2 to 8 hours; and / or, Preferably, the mass ratio of maleic anhydride monomer to styrene monomer is (0.05-1):1; and / or, Preferably, the mass ratio of acrylonitrile to styrene monomer is (0.1-2):1; and / or, Preferably, the temperature of the hydrolysis reaction is 20 to 40° C., and the time of the hydrolysis reaction is 1 to 3 hours; and / or, Preferably, the mass ratio of water to styrene monomer is (0.5-5):1; and / or, Preferably, the mass ratio of the neutralizer to the styrene monomer is (0.05-5):
1.
9. The preparation method according to claim 7, characterized in that: The aqueous emulsifier is prepared by the following steps: polyethylene glycol, bisphenol A epoxy resin, and potassium persulfate are mixed at 100 to 150° C. and reacted for 1 to 10 hours; Preferably, the polyethylene glycol is at least one of polyethylene glycol-200, polyethylene glycol-400, polyethylene glycol-600, polyethylene glycol-800, polyethylene glycol-1000, polyethylene glycol-1500, polyethylene glycol-2000, and polyethylene glycol-4000; the bisphenol A epoxy resin is at least one of E-44, E-51, and E-55; and / or, Preferably, the mass ratio of polyethylene glycol to bisphenol A epoxy resin is (0.5-5):1; and / or, Preferably, the mass ratio of potassium persulfate to bisphenol A epoxy resin is (0.005-0.05):
1.
10. Use of the styrene-acrylonitrile-maleic anhydride copolymer sizing agent according to any one of claims 1 to 4 or the sizing agent prepared by the method according to any one of claims 5 to 9 in fiber composite materials.
Citation Information
Patent Citations
Low yellowness styrene-acrylonitrile-maleic anhydride copolymer and preparation method thereof
CN109021156A